RELEVANSI KOMPETENSI PENDIDIK MENURUT K.H. HASYIM ASY’ARI DENGAN UU SISDIKNAS TAHUN 2003 - Sholikah Sholikah (Al Hikmah: Jurnal Studi Keislaman, 2017)
In general, character education now is still at the level of memorization and/or introduce a value but has not reached the appreciation of values level, even it ​​makes a personal commitment in life. Therefore, it is requiring in-depth review of the educational character from some classical and modern literature that will contribute to such thinking. If we review the book Adab al-'Alim wa al-Muta'allim work of K.H. Hasyim Asy’ari, there is a treatise on education that includes character education, especially about the character values ​​that should be owned by both educators and learners. Starting from the above problems, it becomes urgent to do this research. The focus of this study is how does a character educator by K.H. Hasyim Asy’ari?. Character of educators and learners by K.H.Hasyim Asy’ari in the book Adab al-'Alim wa al-Muta'allim can be classified into three sections include: a. Mental attitude or character that must have teachers and students; b. Efforts are done to be the teachers and students who have character; c. Teaching strategies that done by teachers and learners learning strategies. The third section has the indicators according to the competency of educators, according to the National Education Law of 2003 according to the Center of Education Curriculum Development and Culture. Akarhanaf. 1950. Kiai Hasjim Asj’ari Bapak Ummat Islam Indonesia. Jombang: Pondok Pesantren Tebuireng Asmani, Jamal Ma’mur. 2011. Buku Panduan Internalisasi Pendidikan Karakter di Sekkolah. Jogjakarta: DIVA Press Asy’ari, K.H.M. Hasyim. 2007. Etika Pendidikan Islam; Petuah K.H.M. Hasyim Asy’ari untuk Para Guru (Kyai) dan Murid (Santri), terj. Mohamad Kholil. Yogyakarta: Titian Wacana ___________________. 2011. Menggapai Sukses dalam Belajar dan Mengajar, terj. M. Tholut Mughni. Jombang: Multazam Press ___________________. 1415 H. Adab al-‘Alim wa al-Muta’allim. Jombang: Turats al-Islamy Furqan, Arief. 1992. Pengantar Metode Penelitian Kualitatif. Surabaya: Usaha Nasional Hasan, M. Iqbal. 2002. Pokok-Pokok Materi Metodologi Penelitian. Jakarta: Ghalia Indonesia Khuluq, Lathiful. 2008. Fajar Kebangunan Ulama; Biografi K.H. hasyim Asy’ari. Cet. III. Yogyakarta: LKIS Mas’ud, Abdurrahman. 2006. Dari Haramain ke Nusantara; Jejak Intelektual Arsitek Pesantren. Jakarta: Kencana Masrawi, Zuhairi. 2010. Hadratussyaikh Hasyim Asy’ari; Moderasi, Keutamaan, dan Kebangsaan. Jakarta: KOMPAS Media Nusantara Nata, Abuddin. 2005. Tokoh-Tokoh Pembaruan Pendidikan Islam di Indonesia. Jakarta: Raja Grafindo Persada Muhaimin dan Abdul Mujib. 1993. Pemikiran Pendidikan Islam; Kajian Filosofis dan Kerangka Operasionalnya. Bandung: Trigenda Karya Muhaimin. 2007. Pengembangan Kurikulum Pendidikan Islam di Sekolah, Madrasah, dan Perguruan Tinggi. Jakarta: Raja Grafindo Persada Noor, Rohinah M. 2010. KH. Hasyim Asy’ari Memodernisasi NU dan Pendidikan Islam. Cet. II. Jakarta: Grafindo Khazanah Ilmu Partanto, Pius A. dkk., 1994. Kamus Ilmiah Populer. Surabaya: Arkola Pitono, Djoko dan Haryono, Kun. 2010. Profil Tokoh Kabupaten Jombang. Cet. 3. Jombang: Pemerintah Kabupaten Jombang Ramayulis, dkk., 2011. Filsafat Pendidikan Islam; Telaah Sistem Pendidikan dan Pemikiran Para Tokohnya. Cet. III. Jakarta: Kalam Mulia Rifa’i, Muhammad. 2010. K.H. Hasyim Asy’ari; Biografi Singkat 1871-1947. Cet. III. Jogjakarta: Garasi House of Book Salam, Solichin. 1963. K.H. Hasjim Asj’ari; Ulama Besar Indonesia. Jakarta: Jaya Murni Soekardi, Heru. 1980. Kiai Haji Hasyim Asy’ari. Jakarta: Depdikbud Suwendi. 2004. Sejarah dan Pemikiran Pendidikan Islam. Jakarta: PT. Raja Grafindo Persada Tafsir, Ahmad.2006. Filsafat Pendidikan Islami, Integrasi Jasmani, Rohani dan Kalbu Memanusiakan Manusia. Bandung: Rosdakarya Offset Undang-Undang Republik Indonesia Nomor 20 tahun 2003 tentang Sistem Pendidikan Nasional. 2009. Bandung: Citra Umbara, UU Sisdiknas 2003 UU RI No. 20 tahun 2003 Bab I Pasal I point 5 dan 6 Wahid, Salahuddin. 2011. Transformasi Pesantren Tebuireng; Menjaga Tradisi di Tengah Tantangan. Malang: UIN MALIKI Press Yasin, Fatah. 2008. Dimensi-Dimensi Pendidikan Islam. Malang: UIN-Malang Press Yunus, Mahmud. 1990. Kamus Arab-Indonesia. Jakarta: Hidakarya Agung Zed, Mestika. 2008. Metode Penelitian Kepustakaan. Jakarta: Yayasan Obor Indonesia Zuhri, Achmad Muhibin. 2010. Pandangan Hasyim Asy’ari tentang Ahl al-Sunnah wa al-Jama’ah. Desertasi. Surabaya: Program Pascasarjana IAIN Sunan Ampel Surabaya